The Noise Generated from the Lower Part of Shinkansen Cars Running at High-Speed - KURITA, Takeshi; NAGAKURA, Kiyoshi; KITAGAWA, Toshiki (Journal of Environment and Engineering, 2012)
In order to reduce Shinkansen noise, it is important to develop appropriate countermeasures for pantograph noise and the noise generated from the lower part of cars. The noise generated from the lower part of cars mainly consists of aerodynamic noise and rolling noise. In this paper, firstly, the contribution of rolling noise is quantitatively examined by using measured data of rail vibration and the TWINS (Track-Wheel Interaction Noise Software) model. Next, the contribution of aerodynamic noise to the noise generated from the lower part of cars is determined by a comparison of measured noise and predicted rolling noise. It is apparent that, through this study, the aerodynamic noise has a much greater contribution to the noise generated from the lower part of cars above 335km/h.